LIGAND BASED PHARMACOPHORE MODELING AND QSAR ANALYSIS OF HETEROCYCLIC DIAMIDINE DERIVATIVES AS ANTI-PARASITIC DNA MINOR GROOVE BINDERS - Subhadip Banerjee; Anil Kumar Saikia (Exploratory Animal and Medical Research, 2013)
Ligand based pharmacophore modelling (LBPM) of a group of 26 heterocyclic diamidine derivatives having clinical bioactivity against Trypanosoma brucei gambiense (TBG). A four point pharmacophore model of anti-parasitic diamidines has been developed. Positive ionic and aromatic features were identified as crucial features for showing bioactivity as DNA binders. A statistically feasible 3D QSAR model was developed for further evaluation of the developed pharmacophore model. The good predictive ability of the model has been examined by various statistical parameters like Q2=0.67, r2 pred=0.96 value. This model can be used for in silico screening and designing of potent antiparasitic molecules.